2018
DOI: 10.1088/2057-1976/aab0db
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the biological impact of increased scattered radiation in single and composite field radiation beams

Abstract: Low energy scattered particles cause the average energy at the treatment field edge to be lower relative to the center of the beam. These particles have a higher LET, making them more biologically damaging. With a single beam (large field-size (FS)), the amount of these highly damaging electrons is low relative to within the treatment beam. However, when multiple beam angles and smaller FS are used (IMRT/VMAT), the relative contribution of scattered radiation increases and biological consequences may vary. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
1
1

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…With the advent of new technologies in radiation therapy, such as IMRT, the highly damaging component may be causing more damage than previously thought. [18][19][20][21][22] For particle therapies such as protons, a generic weighting factor of 1.1 is used. This means that in patients, it is assumed that protons are 10% more damaging than photons emitted by cobalt-60.…”
Section: Figure 17mentioning
confidence: 99%
See 3 more Smart Citations
“…With the advent of new technologies in radiation therapy, such as IMRT, the highly damaging component may be causing more damage than previously thought. [18][19][20][21][22] For particle therapies such as protons, a generic weighting factor of 1.1 is used. This means that in patients, it is assumed that protons are 10% more damaging than photons emitted by cobalt-60.…”
Section: Figure 17mentioning
confidence: 99%
“…Since RBE variation under low-dose conditions was examined, the maximum RBE, RBE M was the quantity of interest. In this study, the approach used by Nusrat et al 22 was used to generate RBE M . According to the theory of dual radiation action, the monoenergetic electron α/β can be obtained through:…”
Section: Calculating Relative Biological Effectiveness (Rbe)mentioning
confidence: 99%
See 2 more Smart Citations
“…Since the photon energies used in EBRT are relatively high, the variation of relative biological effectiveness (RBE) is usually minimal. It has been demonstrated that maximum RBE can change by up to 16% when complex beam cases are used due to the presence of increased scattered (low energy) radiation [3].…”
Section: Introductionmentioning
confidence: 99%